Enhancing medical undergraduate training in India: Insights into the prevention and management of noncommunicable diseases - Arohi Chauhan; Pranab Mahapatra; Maulik Chokshi; Tushar Mokashi; Sanghamitra Pati (International Journal of Noncommunicable Diseases)
Introduction: Noncommunicable diseases (NCDs) are becoming significant global health challenges, especially in developing countries like India. Addressing the rising burden of NCDs necessitates systemic changes in healthcare systems, with a particular focus on the training of healthcare providers (HCPs). Integrating NCD prevention and management strategies into medical education are essential for effectively combating this growing public health issue in India. Methodology: A qualitative inquiry was conducted to explore the perspectives of key informants on NCD prevention and management training among medical undergraduates in India. Data were collected through in-depth interviews with stakeholders, including medical educators, healthcare professionals, and policymakers, and analyzed thematically to identify key insights. Results: Findings reveal an urgent need to incorporate NCD prevention and management into the medical curriculum in response to the rising prevalence of multimorbidity in India. Participants emphasized the necessity of curricular or co-curricular components dedicated to NCD prevention. In addition, the study highlighted the importance of creating a supportive environment and fostering a positive climate for NCD prevention and management. Capacity building for medical educators emerged as a critical requirement to ensure they possess the skills and expertise needed to effectively deliver NCD-related training. Conclusion: Given the escalating burden of NCDs in India, there is a pressing need to integrate NCD prevention and management into medical education. Curriculum reform, enabling environments, and capacity-building for medical educators are vital to preparing future HCPs to manage and prevent NCDs at the community level.